Ecological Education as a Strategy for Optimizing Education Service Standards - Wulansari Vitaloka; Alrizka Hairi Dilfa; Dwi Setyorini (Buana Pendidikan, 2022)
The key to the progress of a nation is through education. The benchmark for the success of a good education system arrangement is when educational institutions make the National Education Standards an indicator of Quality and Educational Services. Therefore, the purpose of this article is to identify Education Ecology in improving educational service standards and implementation strategies in education through synergy with educational ecology. The research method used is descriptive with a literature review. The data obtained were collected through the literature related to content analysis. The accuracy of the study and preventing misinformation in data analysis is then carried out by triangulation between literature review and member checking. This study obtained information about the ecology of education to achieve the quality of Education Service Standards. Education Service Standards are basic services, which are public services containing a mandate that contains main points as signs or guidelines in the implementation of education. Ecology offers a conception of the MSS-Education implementation strategy through synergy between each component in the education ecosystem. In other words, the environment is an important consideration in optimizing the implementation of education in Indonesia.